A three-term reciprocity formula for bernoulli polynomials - He, Yuan; Zhang, Wenpeng (Utilitas Mathematica, 2016)
In this paper, by applying the generating function methods and some combinatorial techniques, a three-term reciprocity formula for Bernoulli polynomials is established and some known results are obtained as special cases.